EXPLORING THE IMPACT OF PLP COURSE ON CAREER PERSPECTIVES OF STUDENTS WITH NO INTEREST IN BECOMING ENGLISH TEACHERS - Tria Nova; Nova Lingga Pitaloka (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
Limited studies have investigated how School Field Introduction Program (PLP) shapes English Education students’ perspectives on the teaching profession, particularly those without interest in this profession. Thus, this study aims to explore the perceptions of English Education Students without interest in becoming teachers, focusing on their views before and after participating in the School Field Introduction Program (PLP). This study was conducted in the English Education Study Program at Sriwijaya University, where seven eighth-semester students were involved. This study used qualitative method, particularly a case study. Data were collected using interviews and analyzed using thematic analysis to examine their experiences and perceptions of the teaching profession. The findings revealed that before joining the PLP program, students’ perspectives on the teaching profession were generally mixed, as their initial motivations and career goals were influenced by practical concerns such as responsibilities, financial considerations, and career requirements, as well as by personal experiences and how society perceives teachers. After participating in the PLP program, students’ perspectives on the teaching profession became more informed and reflective, with clearer attitudes toward pursuing or not pursuing teaching as a career, a stronger appreciation of the PLP program’s effectiveness in shaping their understanding of the profession, and constructive suggestions for improving future teacher preparation programs.